Description of Cognitive Function in Type 2 Diabetes Mellitus Patients - Handayani, Eriska Nur; Pebrianti, Sandra; Sumarni, Nina (Indonesian Journal of Global Health Research, 2024)
Cognitive dysfunction is one of the complications of type 2 DM caused by insulin resistance, hyperglycemia, and hypoglycemia. Cognitive impairment in patients results in problems with memory, psychomotor speed, and frontal or executive lobe function. It affects patients' ability to manage self-care, including blood glucose monitoring and foot care. This study aims to identify the cognitive function of patients with type 2 DM. The research used descriptive design with quantitative methods and purposive sampling techniques. The population in this study was 46 patients with type 2 DM in RSUD Sumedang with a sample of 41 people. The instrument used is MoCA-INA to measure the cognitive function of patients with type 2 DM. Data analysis used univariate and frequency distribution The results of the study showed that type 2 DM patients had mild cognitive impairment of 26 (63.4%), severe cognitive impairments of 9 (22.0%), and normal cognitive function of 6 (14.6%). Cognitive impairment in diabetic patients has the potential to affect self-care management, so if not properly maintained, it can worsen the condition of diabetes patients and even lead to death. Therefore, nursing care should enhance education regarding cognitive impairments, regular monitoring and assistance, as well as the use of technology to remind patients of the timing of treatment and self-care.